1998
DOI: 10.1046/j.1365-2249.1998.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressive activity ofAscaris suumis due to high molecular weight components

Abstract: SUMMARYThe role of isolated components obtained by gel filtration chromatography of Ascaris suum body extract (Asc) on the modulation of the immune response to ovalbumin (OvA) was evaluated and correlated with the immunogenic properties of such components. We showed that high (PI), but not low (PIII), molecular weight components have the ability to inhibit OvA-induced immediate and DTH reactions, lymph node (LN) cell proliferation, cytokine (IL-2, interferon-gamma (IFN-g), IL-4 and IL-10) and antibody (IgG1, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
4
41
0
1
Order By: Relevance
“…As shown here, this cytokine, which is induced in large amounts by PI components [12], is a major effector molecule in the down-regulation of MHC and costimulatory molecules in our model, because in the complete absence of IL-10 (IL-10-KO mice) the down-regulation simply did not occur. Furthermore, the Ag-presenting ability of DC was not impaired when these cells were obtained from IL-10-deficient mice immunized with OVA+PI, indicating that, in the absence of this cytokine, DC were functionally preserved from the suppressive effects of PI.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…As shown here, this cytokine, which is induced in large amounts by PI components [12], is a major effector molecule in the down-regulation of MHC and costimulatory molecules in our model, because in the complete absence of IL-10 (IL-10-KO mice) the down-regulation simply did not occur. Furthermore, the Ag-presenting ability of DC was not impaired when these cells were obtained from IL-10-deficient mice immunized with OVA+PI, indicating that, in the absence of this cytokine, DC were functionally preserved from the suppressive effects of PI.…”
Section: Discussionmentioning
confidence: 55%
“…We have previously shown that Asc or PI have the same ability as a live infection to strongly suppress the immune response and to induce a typical Th2 response (with IL-4 and IL-10 secretion) which is responsible for the suppressive effect [10][11][12][13][14]. Concerning the mechanisms involved in this effect, we investigated in this work the hypothesis that PI components could act in the inductive phase of the immune response, modulating the Ag presentation process by APC, and consequently T cell activation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to the nematode Ascaris suum, the regulatory mechanisms induced by its immunosuppressive components have been the focus of our studies for some time. These components correspond to the high molecular weight fraction, eluted in the first peak (PI), after gel filtration chromatography of the adult Ascaris suum body extract 5 . In mice, when PI was combined with ovalbumin (OVA) and adjuvant, both OVA-specific Th1 and Th2 immune responses were found to be impaired (lymphoproliferation, delayed-type hypersensitivity (DTH) reactions, IgG2a/IgG1/IgE and IL-2/ IFN-γ/IL-4/IL-10 production) 5 .…”
mentioning
confidence: 99%